2014
DOI: 10.1021/jo501142q
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Total Synthesis of (+)-Didemniserinolipid B via Achmatowicz Rearrangement/Bicycloketalization

Abstract: A new synthetic strategy was developed for the asymmetric total synthesis of (+)-didemniserinolipid B in 19 linear steps, featuring a highly efficient and enantioselective construction of 6,8-dioxabicyclo[3.2.1]octane (6,8-DOBCO) framework via a rarely explored Achmatowicz rearrangement/bicycloketalization strategy. In addition, the first total synthesis of the proposed (+)-didemniserinolipid C was accomplished with 41.6% yield in 4 steps from a common advanced intermediate 18, and a possible revised structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…846 Syntheses of the reported structures of polycitorols A and B (unidentied ascidian) 847,848 and (+)-didemniserinolipid C (Didemnum sp.) 849,850 suggest that the structures of all three MNPs require revision. Total synthesis has also led to revision of the structure of mandelalide A (Lissoclinum sp.)…”
Section: Molluscsmentioning
confidence: 99%
“…846 Syntheses of the reported structures of polycitorols A and B (unidentied ascidian) 847,848 and (+)-didemniserinolipid C (Didemnum sp.) 849,850 suggest that the structures of all three MNPs require revision. Total synthesis has also led to revision of the structure of mandelalide A (Lissoclinum sp.)…”
Section: Molluscsmentioning
confidence: 99%
“…The oxidation of 2-(trimethylsilyl)furans with mCPBA produces furan-2(3H)-ones. Jia and co-workers used this reaction during their enantioselective synthesis of (-)-pallavicinin (131). They obtained compound 127 starting from furan (126) and then oxidized it with mCPBA to afford unstable furanone 128.…”
Section: Syn Thesismentioning
confidence: 99%
“…Unfortunately, they failed to synthesize this O-sulfate to prove their hypothesis. 131 Tong et al reported the total synthesis of (+)-attenol B starting from furan 345, which was converted into 2-(1,2dihydroxyalkyl)furan 346. Oxidation followed by acidic treatment produced dioxabicyclic compound 347.…”
Section: Scheme 80 Formal Synthesis Of Tirandamycin Bmentioning
confidence: 99%
“…104-107 The issues related to the use of bromine and poor water solubility of pyran-3-ones, prompted the development of new non-bromine-based oxidizing agents such as m -CPBA in a variety of solvents. 108-113 This alternative furylcarbinol ring expansion was nicely employed in natural product total syntheses. 114-117 …”
Section: Introductionmentioning
confidence: 99%
“…180 Tong and co-workers utilized an Achmatowicz reaction in the total synthesis of (+)-didemniserinolipid B ( 96 , Scheme 26) in 19 steps from commercially available materials. 108 In particular, the target compound was assembled from the 6,8-DOBCO system ( 97 ). 181-183 The key 6,8-DOBCO fragment 97 was envisioned from hydrogenation and diastereoselective ketone reduction of the bicyclic acetal 98 .…”
Section: Introductionmentioning
confidence: 99%